2018
DOI: 10.18843/ijcms/v9i3/02
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Business Incubators in Creating an Entrepreneurial Ecosystem: A Study of the Sultanate of Oman

Abstract: New entrepreneurs have to face multiple challenges in starting, growing and sustaining their businesses. In developing countries, these challenges can range from labour and market regulations, finding the right markets for products, finding appropriate sources of funding, education and training of entrepreneurs and a lack or R&D infrastructure (Shanfari, D., 2012). Many small businesses fail in the initial stages as the owners are unable to negotiate and find solutions to these multifarious challenges. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 12 publications
0
24
1
Order By: Relevance
“…It is widely recognized that business incubators play a vital role in contributing to the country's economy on a local, regional, national and global level (Campbell, 1989;AL Mubaraki, 2008;Ndabeni, 2008;Al Mubaraki et al, 2010;Dee et al, 2011;Lewis et al, 2011;Lose et al, 2016). Business Incubators have a positive impact on economic development and sustainability through job creation across different countries such as Oman, USA, China and Europe (Sanyal and Hisam, 2018;Wagner, 2006;Lalkaka, 2002;Ogutu and Kihonge, 2016). Moreover, Mahmood et al, (2015) and Markley and McNamara (1995) further confirmed that business incubators played a crucial role in creating, nurturing and sustaining SMEs in the local economy and in turn developing the economy of a nation.…”
Section: Business Incubators and Economic Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…It is widely recognized that business incubators play a vital role in contributing to the country's economy on a local, regional, national and global level (Campbell, 1989;AL Mubaraki, 2008;Ndabeni, 2008;Al Mubaraki et al, 2010;Dee et al, 2011;Lewis et al, 2011;Lose et al, 2016). Business Incubators have a positive impact on economic development and sustainability through job creation across different countries such as Oman, USA, China and Europe (Sanyal and Hisam, 2018;Wagner, 2006;Lalkaka, 2002;Ogutu and Kihonge, 2016). Moreover, Mahmood et al, (2015) and Markley and McNamara (1995) further confirmed that business incubators played a crucial role in creating, nurturing and sustaining SMEs in the local economy and in turn developing the economy of a nation.…”
Section: Business Incubators and Economic Developmentmentioning
confidence: 99%
“…These types of incubators support and assist SMEs in the manufacturing industry and tend to offer physical and production space and technical business assistance (Sanyal and Hisam, 2018;Al Mubartaki et al, 2010).…”
Section: Manufacturing/indus Trial Incubatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forming the conditions for interaction, the business incubator is an ecosystem for the implementation of innovative projects, which allows using the potential of all entities of the virtual platform on the basis of integration processes and the integrated use of information technologies [49,50]. Thus, by combining conditions and resources, a controlled environment is created that allows business projects at any stage to effectively develop.…”
Section: Developing the Interaction Mechanismmentioning
confidence: 99%
“…The establishment and encouragement of new businesses in a community is the main goal of BIs. In assisting entrepreneurs to start new businesses, the community enjoys benefits of increased employment opportunities, additional revenue, and prosperity (Sanyal & Hisamic, 2018).…”
Section: Business Incubation In the Kingdom Of Eswatinimentioning
confidence: 99%